Extinction or evolution? Changes in in-house translators’ work in Finland in 1995–2018 - Hjort Minna; Ruokonen Minna (Suomen kääntäjien ja tulkkien liitto ry, 2025)
Since the 1990s, outsourcing, streamlining and technologisation have induced profound changes in the content, organisation and location of translators’ work. Nevertheless, due to the scarcity of longitudinal research, such changes must typically be pieced together from individual studies. The present paper adopts a novel approach: analysing data from a survey in which the respondents (n=223) could report on one current and two previous in-house positions, we provide an overview of the changes in in-house translators’ work in Finland from 1995 to 2018. Combining quantitative and qualitative methods, we consider 1) indications of outsourcing and restructuring, 2) changes in responsibilities and 3) changes in physical location and organisational position. The responses indicate some decrease in in-house jobs and a greater variety in responsibilities. There is also an increase in teleworking and indications of complex organisational structures, although translation teams remain common. On the whole, in-house translators appear an evolving rather than an endangered professional group.